Paramorphology and Lexicogenesis: an impossible portmanteau? - Casas Navarro, Raymundo (2020)
We propose to elucidate the internal mechanisms of the dynamic process of lexicogenesis, with special emphasis on the term ‘feminazi’ (recently coined in Spanish from the English language). It is a portmanteau that, by integrating the words ‘feminist’ and ‘Nazi’, a new word with a strong pejorative sense is elaborated. This new word is frequently used in different areas, especially in the polemic forums of social networks. Due to its pervasive ideological connotations, a sort of sociolectal isogloss has been built: while a group of speakers considers it a poisonous portmanteau that deserves banishment from the idiomatic use because it inserts itself into a hate speech, another group of speakers considers it to be basically adequate. From the theory and methodology of the conceptual fusion inscribed in the domain of modern cognitive semantics, we will explore the nature of the underlying projections in the portmanteau, and we will try to obtain a plausible conclusion about the semantic emergence of the word. By virtue of the semantic-cognitive analysis, we will be able to explain the bifurcation in the perspectives of the pugnacious portmanteau.